DEVELOPMENT OF DIGITAL MEDIA SILIR (SIKLUS AIR) TO INCREASE LEARNING INTEREST OF GRADE IV STUDENTS OF SDN 5 CENDONO - fenita khairani khairani; Fina Fakhriyah Fakhriyah; Denni Agung Santoso Santoso (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to (1) determine the feasibility of SILIR learning media, and (2) the effectiveness of SILIR learning media on learning interest. This research uses the ADDIE model, with stages of analysis, design, development, implementation, and evaluation. The research subjects were 20 fourth grade students of SDN 5 Cendono, Dawe District, Kudus Regency. Data were collected through observation, interview, validation questionnaire, teacher and student response questionnaire, and learning interest questionnaire. The data were analyzed qualitatively and quantitatively to assess the feasibility of the product. The results showed that the needs analysis of students preferred visual and game-shaped media. SILIR media received a high feasibility score of 99% from media experts and 89% from material experts. Teacher and student responses were also positive, with scores of 90% and 91% respectively. In addition, students' interest in learning increased from 44% in the pre-test to 91% in the post-test, or an increase of 47%. Thus, SILIR media is effective in increasing learning interest.